How Africa’s cotton markets could help to boost continental growth - Odjo, Sunday; Traore, Fousseini; Zaki, Chahir (African Business, 2023)
Can Africa’s cotton sector also become a major export revenue source for the continent and boost continental growth? The editors of Africa Agriculture Trade Monitor look at the steps that need to be taken.